Effects of hexavalent chromium on phytoplankton and bacterioplankton of the Río de la Plata estuary: an ex-situ assay - Sathicq, María Belén (2018)
We examined the responses of the phytoplankton and the bacterioplankton of the freshwater zone of the Rio de la Plata estuary when exposed to an addition of hexavalent chromium (Cr⁺⁶). The planktonic community from a coastal site was exposed to a chromium increase of 80 μg L⁻¹ for 72 h in laboratory conditions. The results showed a decrease in the concentration of Cr⁺⁶ by 33% in the treatments, along with significant decreases in chlorophyll-a (63%), the chlorophyll-a:pheophytin-a ratio (33%), oxygen production (37%), and in the total density of the phytoplankton (15%). The relative abundance of chlorophytes and diatoms decreased, while the cyanobacteria thrived. Finally, the total bacterial density and the density of viable bacteria decreased. These results show that even small increments in Cr⁺⁶ can cause significant effects on the phytoplankton and bacterioplankton, which could potentially affect other trophic levels of the community, risking alterations of the entire ecosystem.